2016
DOI: 10.1007/s11442-016-1272-5
|View full text |Cite
|
Sign up to set email alerts
|

Progress on quantitative assessment of the impacts of climate change and human activities on cropland change

Abstract: Abstract:It is important to study the contributions of climate change and human activities to cropland changes in the fields of both climate change and land use change. Relationships between cropland changes and driving forces were qualitatively studied in most of the previous researches. However, the quantitative assessments of the contributions of climate change and human activities to cropland changes are needed to be explored for a better understanding of the dynamics of land use changes. We systematically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 43 publications
0
12
1
1
Order By: Relevance
“…This study's conclusion differs from the conclusions of prior studies, which report that the development of urbanization pushes cropland abandonment in mountainous areas [51,68]. The possible reasons for this different result are as follows: as the margins of urban areas continue to expand, cropland gradually moves to higher altitudes [71]. Thus, mountainous cropland becomes important to ensure global food security.…”
Section: Discussioncontrasting
confidence: 92%
“…This study's conclusion differs from the conclusions of prior studies, which report that the development of urbanization pushes cropland abandonment in mountainous areas [51,68]. The possible reasons for this different result are as follows: as the margins of urban areas continue to expand, cropland gradually moves to higher altitudes [71]. Thus, mountainous cropland becomes important to ensure global food security.…”
Section: Discussioncontrasting
confidence: 92%
“…In terms of regional selection, studies have been carried out in regions where the coupling effect between vegetation and climate change and human activities is typical within the fluctuation area of the 400 mm annual precipitation line, for example on the Loess Plateau [14][15][16], in the northeast of China [17,18], on the Qinghai-Tibet Plateau [19][20][21]. Shi et al [22] have found that climate change and human activities had a significant driving effect on the boundary change of the northern farming-pastoral ecotone, and some studies quantitatively analyzed the impacts of climate change and human activities on arable land [23,24]. Sun et al [25] have found that vegetation coverage on the Loess Plateau showed a significant upward trend in the past three decades under the influence of human activities, mainly ecological restoration projects.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, it is necessary to consider comprehensively runoff production and dissipation, mountains and plains, and deserts and oases when producing land surface parameterization improvement programs; to develop a multi-scale and multi-objective hydrological model merging method; to construct a mountains-oases-deserts coupling, distributed regional water cycle model with land pattern features that fit arid areas and a river basin hydrological and water resource model based on mountain meltwater and precipitation. This allows quantitative identification of the impact of climate change and human activities on the water resource systems of arid areas (Li et al, 2016b;Shi et al, 2016), investigation of the possible major effects of spatio-temporal changes to water resources on socio-economic systems and ecosystems in arid areas, and predictions of scientific water cycle laws and water resource changing trends for arid areas.…”
Section: Bi-directional Coupling Of High-resolution Regional Climate mentioning
confidence: 99%